2015
DOI: 10.1007/s10897-015-9839-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practice Regarding Genetic Testing and Genetic Counselors in Jordan: A Population‐Based Survey

Abstract: Genetic testing has a potential in the prevention of genetic diseases, particularly in communities with high rates of consanguineous marriage. Therefore, knowledge, practice, and attitudes of the public in Jordan regarding genetic testing were investigated. Individuals (N = 3,196) were questioned about the concepts of genetic testing and genetic counselors, if they underwent any genetic tests, the type of test, the method of consenting to the test, as well as their level of satisfaction with the privacy of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
2
23
1
1
Order By: Relevance
“…In the present study, the proportion of respondents who had prior knowledge of genetic testing was much higher than that reported in prior studies conducted in other countries [3,7,8,23]. Phuong et al indicated that 47% (95% CI 46.1-48.0%) of the U.S. population was aware of genetic testing.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In the present study, the proportion of respondents who had prior knowledge of genetic testing was much higher than that reported in prior studies conducted in other countries [3,7,8,23]. Phuong et al indicated that 47% (95% CI 46.1-48.0%) of the U.S. population was aware of genetic testing.…”
Section: Discussioncontrasting
confidence: 80%
“…Consequently, identifying differences in viewpoints on genetic testing has grown in importance, and studies have begun to assess awareness and attitudes toward genetic testing among people throughout the world [1,[3][4][5][6][7][8][9][10][11]. Overall, most of these studies have focused on particular demographic groups or specific medical conditions, and while recent literature reviews suggest that public attitudes toward genetic testing are positive, they have been found to vary according to sex, age, education level, health status, etc [4].…”
Section: Introductionmentioning
confidence: 99%
“…This fear may be intensified and more common in this ethnic group because of the frequent practice of the family vetting potential marriage partners for suitability, fertility and character [29,30]. In addition, some Arab countries have a mandatory pre-marital genetic testing due to the high rates of consanguineous marriage and the increased transmission rates of autosomal recessive disorders, such as β-thalassemia [44]. In contrast, women with limited access to information perhaps focus more on their fear that breast cancer is contagious, and thus perceive themselves to be a risk to their family's physical well-being.…”
Section: Discussionmentioning
confidence: 99%
“…GnomAD, ClinVar, OMIM, COSMIC y Human Gene Mutation Database son bases de datos confiables para examinar la asociación de una variante a enfermedad (tabla 2) (33). Este proceso de interpretación deberá ser realizado idealmente por el laboratorio como parte de su servicio y explicado al paciente por profesionales con entrenamiento calificado en asesoría genética (40). En caso de que todavía existan dudas sobre la significancia clínica de los hallazgos o aún no se hayan identificado variantes que expliquen la clínica del paciente, se puede considerar como opción la secuenciación de los familiares del paciente para ayudar a clarificar la relación de la presencia de una variante con la presentación de la enfermedad (41).…”
Section: Aspectos éTicos Y Normatividad Sobre El Reporte Interpretacunclassified